2015
DOI: 10.1186/s40323-015-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the separated approximation of input data in the accuracy of the resulting PGD solution

Abstract: The proper generalized decomposition (PGD) requires separability of the input data (e.g. physical properties, source term, boundary conditions, initial state). In many cases the input data is not expressed in a separated form and it has to be replaced by some separable approximation. These approximations constitute a new error source that, in some cases, may dominate the standard ones (discretization, truncation…) and control the final accuracy of the PGD solution. In this work the relation between errors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Thus, the error of PGD approximation compared with the analytical solution is always larger than the FE error. () In this example, the influence of the polynomial degree on the interface polynomials, the number of modes used in the PGD approximation, and the mesh discretization in the final error is studied.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Thus, the error of PGD approximation compared with the analytical solution is always larger than the FE error. () In this example, the influence of the polynomial degree on the interface polynomials, the number of modes used in the PGD approximation, and the mesh discretization in the final error is studied.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Nevertheless, the selected loading locations may not necessarily be the subset of the spatial nodes. In this case, we would like to point out that proper selections of the location of DOF is important for avoiding interpolative instabilities …”
Section: Nonintrusive Pgd Schemementioning
confidence: 99%
“…The next section presents some details on f sep and the error introduced by this separation. A detailed study of how separation of given data affects PGD can be found in [24].…”
Section: Separation Of Input Datamentioning
confidence: 99%
“…The choice of the sampling points T h  has an impact on the convergence of the PGD method as shown in [24]. We compare two different choices.…”
Section: Selection Of Sampling Pointsmentioning
confidence: 99%